2017
DOI: 10.1177/2048872617740833
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of Growth Arrest-Specific 6 protein and soluble AXL in patients with ST-segment elevation myocardial infarction

Abstract: sAXL levels increased following STEMI. Patients with heart failure and left ventricular remodelling have higher sAXL levels acutely and at six month follow-up. These findings suggest a potential role of the GAS6-AXL system in the pathophysiology of left ventricular remodelling following STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…In cardiac transplant recipients, sAXL values were higher in those presenting with adverse CV events, an association that remained significant after multivariate adjustment [18]. After an ST-elevation AMI, higher sAXL levels flag those patients who will develop HF and an adverse LV remodeling during follow-up [19]. We have reported that sAXL is a good prognostic marker of the HF major events all-cause mortality, transplantation and HF hospitalizations at 1 year [20] and at 3.6 years follow-up [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cardiac transplant recipients, sAXL values were higher in those presenting with adverse CV events, an association that remained significant after multivariate adjustment [18]. After an ST-elevation AMI, higher sAXL levels flag those patients who will develop HF and an adverse LV remodeling during follow-up [19]. We have reported that sAXL is a good prognostic marker of the HF major events all-cause mortality, transplantation and HF hospitalizations at 1 year [20] and at 3.6 years follow-up [29].…”
Section: Discussionmentioning
confidence: 99%
“…Gas6 (-/-) mice lacking the Axl-ligand Gas6 are protected from pressure-overload left ventricle (LV) remodeling and fibrosis, while LV remodeling was remarkably increased in mice with Gas6 cardiac overexpression [17]. In humans, sAXL evolves as an attractive biomarker for HF and other cardiac conditions [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with heart failure Axl levels are amplified both in terms of the cardiac tissue and circulating soluble Axl (sAxl) 35 . Furthermore, Gas6 and sAxl levels are found to increase in patients following ST-segment elevation MI 96 . In both studies, the levels of Axl were predictive of adverse pathology, such as the extent of left ventricular remodelling and of further cardiovascular events.…”
Section: Axl In Cvdmentioning
confidence: 97%
“…Although Tyro3 could potentially have a protective effect on the myocardium, as it suppresses Th2 responses which drive cardiac fibrosis, 136 , 140–142 a direct causal link has not been shown to date. Gas6-Axl driven activation of the ERK signalling cascade in cardiomyocytes is implemented in the pathological remodelling which occurs in heart failure patients 35 , 96 , 97 . Numerous studies have highlighted Axl to also have a pathological role in vascular remodelling through increasing VSMC proliferation, migration, and immune activation, while also inhibiting VSMC apoptosis 64 , 65 , 69 , 79 …”
Section: Conclusion and Future Questionsmentioning
confidence: 99%
“…AXL is involved in the angiogenesis regulation. It was found that patients with heart failure and severe left ventricular remodeling processes have a higher level of sAXL, which indicates the potential role of the GAS6-AXL system in the pathophysiology of these processes (Caldentey et al, 2019). Increased AXL expression in arteries was revealed in patients after coronary artery bypass grafting.…”
Section: Discussionmentioning
confidence: 98%